TO THE ISSUE ABOUT SOCIAL FACTORS OF FORMATION OF MODERN UNIVERSITY’S SCIENTIFIC POTENTIAL - D. Yu. Znamenskiy (Вестник университета)
The object of the research is the scientific potential of the modern university, and the subject is the system of social factors of its formation. The purpose of the study is to identify the role of social factors in the development of the scientific potential of the modern university. The methodological basis of the paper is a system-dynamic approach to the study of scientific potential, which consists in the consistent disclosure of its spatial, temporal and technological components. Within the framework of the first component, it is necessary to emphasize such a little-studied aspect as the social foundations of scientific potential, including the system of values of employees and students of the university, their motivation to engage in scientific activity and the level of prestige of scientific activity at the university. The components of the scientific potential of the modern university have been analysed in the article. In particular, the close interrelation of the specified social factors with personnel bases of scientific potential of higher education institution, namely with tendencies of development of its personnel structure has been revealed. A system for assessing the social factors of the scientific potential of the university has been proposed. The results of the study can be used by universities to increase the level of motivation of teaching staff to research activities, as well as the Ministry of Education and Science of Russia – in assessing the research activities of Russian universities.